التهرب الضريبي وآليات مكافحته - بلول, محمد (جامعة الوادي -University eloued, 2017)
تسعى هذه الدراسة إلى الكشف عن ظاهرة التهرب الضريبي التي تفاقمت واتسعت آثارها في السنوات الاخيرة فأصبحت تهدد وجود النظام الضريبي كما تضيع أموال طائلة على الخزينة العمومية مما يترتب عنها انعكاسات سلبية على الاقتصاد الوطني، وهذه الظاهرة لها عدة أشكال منها المشروعة والغير مشروعة وذلك باستغلال ثغرات قانونية. هذه الجريمة التي يشترك فيها عدة إطراف وجب التصدي لها بكل الطرق والآليات وذلك بنشر الوعي التحسيسي بين المكلفين، وذلك لأن للضريبة دور هام وأساسي في إنعاش الخزينة العمومية، وبالتالي إنعاش التنمية الاقتصادية والاجتماعية، وكذا القيام بحملات توعوية وملتقيات بين المكلفين والإدارة، ويجب على المشرع إرساء قوانين دائمة ومستقرة وتحسين الجهاز الإداري وتدعيمه بالوسائل والآليات المادية والبشرية والمتمثلة في كفاءة الأعوان الضريبيين وتوفر الوسائل المساعدة لتحسين وتسهيل العمل الرقابي والمتابعة الميدانية. This study seeks to uncover the phenomenon of tax evasion, which has worsened and widened its effects in recent years, thus threatening the existence of the tax system and wasting large sums on the public treasury, which have negative repercussions on the national economy. This phenomenon has several forms, both legitimate and illegal, . This crime, which involves several parties, must be dealt with in all ways and mechanisms by spreading awareness among the taxpayers. Taxation plays an important role in revitalizing the public treasury, thus stimulating economic and social development, as well as awareness campaigns and forums between the taxpayers and the administration. Permanent and stable laws and the improvement of the administrative system and strengthening it through the means and mechanisms material and human and the efficiency of tax officers and provide the means to help improve and facilitate the monitoring work and follow-up field.
ماستر اعمال
Keywords: الضريبة - التهرب الضريبي- التجنب الضريبي - الغش الضريبي - الإدارة; Tax evasion – Tax fraud – Tax administration – Fiscal control – Tax charged.